PROVING THE EFFICACY OF MANGIFERIN AS A NEUROPROTECTIVE DRUG USING DOCKING STUDIES (Proceedings of International Conference on BioScience and Biotechnology, 2018)
Mangiferin, a bioactive Xanthonoid known for its anti-oxidant & therapeutic activity, has been involved in a variety of potential pharmacological activities. The aim of this work is to prove the efficacy of mangiferin as a neuroprotective drug by docking it with β-amyloid precursor protein, which causes Alzheimer’s. Alzheimer’s disease (AD) is a progressive neurodegenerative disease, which is characterized by progressive cognitive deterioration and behavioral changes along with the chronic inflammation of neurons. Studies have shown that the deposition of amyloid-β (Aβ) peptide has resulted in the inflammatory changes such as astrocytosis and microgliosis. Based on the quantitative analysis of the molecular docking technique it was observed that mangiferin successfully docked with amyloid-β (Aβ) peptide. The ligand binding affinity was high due to the presence of many flexible docked conformers. The most stable conformer was having a final docked value of -12.421 with binding energy amounting to -4.11 kcal/mol. The in silico docking analysis demonstrates that mangiferin exhibits binding interactions with β-amyloid precursor protein that are potentially responsible for the inhibition of the protease enzyme which would be helpful in developing a neuroprotective drug for Alzheimer’s Disease.
Keywords: Mangiferin; β-amyloid peptide (Aβ); Alzheimer’s disease; AutoDock; Binding Energy